2019
DOI: 10.1038/s41419-019-1822-8
|View full text |Cite
|
Sign up to set email alerts
|

Fasting and rapamycin: diabetes versus benevolent glucose intolerance

Abstract: Rapamycin (Sirolimus) slows aging, extends life span, and prevents age-related diseases, including diabetic complications such as retinopathy. Puzzlingly, rapamycin can induce insulin sensitivity, but may also induce insulin resistance or glucose intolerance without insulin resistance. This mirrors the effect of fasting and very low calorie diets, which improve insulin sensitivity and reverse type 2 diabetes, but also can cause a form of glucose intolerance known as benevolent pseudo-diabetes. There is no indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 139 publications
(201 reference statements)
3
44
0
Order By: Relevance
“…4c, d). Consistent with these results, FMD combined with FDFT1 overexpressing had the most significant inhibitory effect on 18 F-FDG uptake in the in the xenograft model ( Fig. 4e, f).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…4c, d). Consistent with these results, FMD combined with FDFT1 overexpressing had the most significant inhibitory effect on 18 F-FDG uptake in the in the xenograft model ( Fig. 4e, f).…”
Section: Resultssupporting
confidence: 85%
“…We confirmed these results in an in vivo xenograft model. Fasting dramatically inhibited 18 F-FDG uptake and attenuated tumor growth in this xenograft model. These results suggested that, similar to traditional cancer therapy, fasting can be a potential therapeutic Fig.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Rapamycin, (International Nonproprietary Name: sirolimus), is an inhibitor of mTOR, which results in an extended life span and prevents age-related diseases [157][158][159][160] by mediating SIRT1 expression [161,162]. mTOR is a serine-threonine kinase that plays a role in modulating cell survival, growth, proliferation, motility, protein synthesis and transcription [163] and inducing autophagy [164][165][166].…”
Section: Rapamycinmentioning
confidence: 99%
“…Next, we investigated the involvement of apoptotic cell-mediated activation of mTORC1 in macrophages producing anti-inflammatory/tissue growth factors. The mTOR inhibitor rapamycin has been widely used to investigate mTORC1 function and signaling 48 50 . KCs that had phagocytosed apoptotic cells showed increased the expression of anti-inflammatory/tissue growth factors Il10 and Hbegf ; in contrast, the expression of these genes was reduced by rapamycin treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%